1996
DOI: 10.3109/09286589609080122
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of corneal ulceration in Madurai District, South India

Abstract: Corneal ulceration is a common occurrence in South India. While the true incidence of this problem is impossible to determine because of the lack of medical records, we believe our estimation of the incidence to be close to the true incidence in this community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
99
7

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(116 citation statements)
references
References 9 publications
10
99
7
Order By: Relevance
“…Among the bacteria isolated, Gram-positive cocci continue to be the most frequent agent, with a similar rate compared to the other studies in both elderly and age-independent series (17,20,26,(28)(29)(32)(33)(34)(35)(38)(39)(40)(41)(42)(43) . The incidence of Gram-negative bacilli was a little higher, which could be explained by geographical variation in the microbial flora of our patients (2,(14)(15)44) .…”
Section: Microbiologysupporting
confidence: 50%
See 1 more Smart Citation
“…Among the bacteria isolated, Gram-positive cocci continue to be the most frequent agent, with a similar rate compared to the other studies in both elderly and age-independent series (17,20,26,(28)(29)(32)(33)(34)(35)(38)(39)(40)(41)(42)(43) . The incidence of Gram-negative bacilli was a little higher, which could be explained by geographical variation in the microbial flora of our patients (2,(14)(15)44) .…”
Section: Microbiologysupporting
confidence: 50%
“…The incidence of different causative agents vary largely according to the geographical region, socioeconomic condition of the population and many individual factors such as contact lens use (3)(4)(5) , history of trauma (6)(7) or past ocular surgery (8)(9)(10)(11)(12)(13) , presence of comorbidities (14)(15)(16) , and age of the patient (17) , among many others. Several studies have been published regarding the epidemiologic aspects of infectious keratitis on the five continents, both in developed and developing countries (18)(19)(20)(21)(22)(23)(24) . Elderly patients are known to have several systemic and ocular peculiarities such as immunologic senescence, comorbidities, alteration of the lids and conjunctival flora, poor lacrimal drainage, fragility of the corneal epithelium, and reduction of corneal sensitivity, among others.…”
mentioning
confidence: 99%
“…By applying the 1993 corneal ulcer incidence rate in Madurai District to all of India, there are an estimated 840 000 people a year in the country who develop an ulcer. This figure is 30 times the number of corneal ulcers seen in the United States (14) . Extrapolating the Indian estimates further to the rest of Africa and Asia, the number of corneal ulcers occurring annually in the developing world quickly approaches 1.5-2 million, and the actual number is probably greater.…”
Section: Epidemiology Of Corneal Ulceration: -mentioning
confidence: 99%
“…Corneal ulceration in developing countries has only recently been recognized as a ''silent epidemic'' (13) . Gonzales et al found that the annual incidence of corneal ulceration in Madurai District in South India was 113 per 100 000 people, see figure 1 (14) , 10 times the annual incidence of 11 per 100 000 reported from Olmsted County, Minnesota, in the United States of America (15) . By applying the 1993 corneal ulcer incidence rate in Madurai District to all of India, there are an estimated 840 000 people a year in the country who develop an ulcer.…”
Section: Epidemiology Of Corneal Ulceration: -mentioning
confidence: 99%
“…Bacterial corneal ulceration is an ocular emergency due to often rapid progression of this corneal infection with the threat of vision loss Keratitis is the term applied for inflammation of the cornea [1]. Corneal infections are known to be the second most significant cause of monocular blindness rated after unoperated cataract in some developing countries in the tropics [2][3][4]. Corneal infection is a leading cause of ocular morbidity and blindness worldwide.…”
mentioning
confidence: 99%